Peningkatan Kesadaran Energi Terbarukan Melalui Sosialisasi dan Pembuatan Lampu Solar Light Tenaga Surya di Desa Jayamulya, Kabupaten Bekasi - Azis, Sokheh Abdul; Sulastri, Tuti; Rofiq, Ainur (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to increase awareness and understanding of the people of Jayamulya Village, Serang Baru District, Bekasi Regency, regarding the use of renewable energy through the installation of solar energy-based public street lighting (PJU). This village faces the problem of minimal street lighting, which has the potential to increase the risk of crime at night. This program aims to provide a sustainable solution by introducing modern technology solar lamps, which are equipped with 300 watt LED lights, 6V/13 watt polycrystalline solar panels, 15000 mAh lithium batteries, radar sensors and LDR sensors for energy efficiency. Implementation methods include outreach, installation training and technical assistance to the community. The results of the activity show that the community is able to understand and install solar-powered lights independently. The application of this technology provides benefits in the form of increased road safety, energy savings and reduced maintenance costs. This activity proves the effectiveness of introducing environmentally friendly technology in supporting sustainable village development.